Tuberculosis Disease Detection Application Using Forward Chaining Method - Vina Yanuar Prasasti; Asep Jamaludin; Didi Juardi (INTECOMS: Journal of Information Technology and Computer Science, 2021)
Developments in expert system technology and the addition of human needs with an accurate health information and ease of human work is very important in daily life sometimes people lack awareness about the wrong lifestyle and diet is always neglected. Until the occurrence of tuberculosis caused by the bacterium mycrobacterium tuberculosis and caused attacks on parts of the lungs, bones, glands and intestines. In the study conducted the creation of tubekrulosis disease detection application using website-based and for the application process there are 16 questions about the symptoms of tuberculosis disease and will come to a conclusion with 4 diagnoses of each tuberculosis disease accurately based on experts. In the creation of this application using forward chaining method, MySQL, DFD and breadth first search.